Trajetórias Imaginadas: representações da juventude negra no cinema brasileiro contemporâneo João Pessoa 2014 - Rodrigues, Ana Ligia Muniz (2014)
This work analyzes the representations of the black youth on the contemporary Brazilian cinema from the movie Bróder! (Jeferson De, 2010), considering that racial tensions that have marked the Brazilian society can be understood from film representations. Reviewing the 2000 s productions, the context of the movie production as a place of its director on the field of national cinema can be highlighted. Through film analysis we could identify the portraits of how it is to be young, black and a resident of the outskirts, exploring the racial tensions present on the work as own aspects of the cinematographic device. This way, the work assumes a perspective that racial relations of a society are also expressed in their cultural productions. This way, cinema is understood as an important way of spreading representations of and about social groups.